A simple surgical treatment for bovine digital dermatitis-associated white line lesions and sole ulcers. Issue 2 (May 2015) - Kofler, J.; Glonegger-Reichert, J.; Dietrich, J.; Sykora, S.; Tichy, A.; Brandt, S.
Highlights: This simple treatment procedure for nhWLD and nhSU can be easily implemented in practice. Regional retrograde anesthesia allows complete removal of loose horn and rigorous surgical debridement of infected tissue. Applying this treatment procedure, an additional systemic antibiotic treatment is not necessary. By 38 days, 71% nhWLD and nhSU had healed and were completely covered by a new horn layer using the described method. Abstract: Non-healing white line disease (nhWLD) and sole ulcers (nhSU) are seen increasingly in herds endemically affected with bovine digital dermatitis (BDD). In 35 cows with 42 nhWLD or nhSU lesions, the healing process was monitored for up to 28 or 38 days following extensive debridement of loose horn and infected corium under regional anaesthesia, and topical application of tetracycline spray with bandaging. By 28 days, 27/42 (64%) nhWLD and nhSU were completely covered by a new horn layer and this increased to 30/42 (71%) that had healed by 38 days. Lesion sizes on day 0 correlated with clinical healing within the study period. In view of this satisfying therapeutic result, the terms nhWLD and nhSU are proposed for BDD-associated white line disease (BDD-WLD) and BDD-associated sole ulcers (BDD-SU), respectively.